Clinical Analysis of Castleman’s Disease of the Lacrimal Gland - Dongping Li; Dongrun Tang; Fengyuan Sun (Journal of Ophthalmology, 2020)
Objective. To explore the clinical manifestations, imaging characteristics, and pathological characteristics of Castleman’s disease of the lacrimal gland, enhance the knowledge of the disease, and improve the level of its diagnosis and treatment. Methods. In the retrospective study, the data of 5 patients diagnosed with Castleman’s disease of the lacrimal gland in Tianjin Medical University Eye Hospital from 2014 to 2018 were analyzed, and the relevant literature was reviewed. Results. All the 5 patients were confirmed by pathological examination. Clinical manifestations were characterized by mass occupying lesions in the lacrimal gland area, without obvious pain, accompanied by eyelid swelling and ptosis, as well as space-occupying symptoms. Imaging examination showed that there was a soft tissue mass in the enlarged lacrimal gland area, and the mass was rich in blood flows while showing no obvious specificity, which could invade the surrounding muscles. All patients underwent surgical resection. Pathological results showed that 1 case was of the hyaline-vascular type, 3 cases were of the plasma cell type, and 1 case showed malignant transformation to plasma cell tumor. Conclusion. Castleman’s disease of the lacrimal gland is a rare orbital lymphoproliferative disease lacking specificity in clinical manifestations and imaging examination. As there are difficulties in differentiating the disease from orbital inflammatory pseudotumor and orbital lymphoma, its diagnosis still depends on pathological examination. The disease is mainly treated with surgical resection, and the pathological type is determined postoperatively.